Joint consensus statement and guideline on transcatheter aortic valve implantation (TAVI) in South Africa - Hellig, Farrel; Cassel, Graham; Kleinloog, Robbie; Mabin, Tom; Sussman, Martin (SA Heart Journal, 2017)
The South African Heart Association (SA Heart) together with its major special interest groups, SASCI and SCTSSA represent the scientific, educational, socio-economic, ethical and professional interest of cardiac specialists, with a combined membership of over 200 members: We are the only national organisations exclusively representing practicing cardiologists and cardiothoracic surgeons. We are dedicated to maintain the highest standards of practice for our specialists and the highest quality of care for patients who require our care. As a result, we seek to serve as a knowledge resource for patients and funders in matters related to new technology used in our disciplines.